Neoadjuvant Multikinase Inhibitor in Patients With Locally Advanced Unresectable Thyroid Carcinoma - Nava, Carla Fernanda; Scheffel, Rafael Selbach; Cristo, Ana Patrícia; Ferreira, Carla Vaz; Weber, Shana; Zanella, André Borsatto; Paixão, Francisco Costa; Migliavaca, Alceu; Guimarães, José Ricardo; Graudenz, Marcia Silveira; Dora, José Miguel; Maia, Ana Luiza (Frontiers in Endocrinology, 2019)
Background: Papillary thyroid carcinoma (PTC) is the most common and less aggressive thyroid cancer, but some patients may display locally advanced disease. Therapeutic options are limited in these cases, particularly for those patients with unresectable tumors. Neoadjuvant therapy is not part of the recommended work up. Methods: Report a case of an unresectable grossly locally invasive PTC successfully managed with neoadjuvant therapy and provide a systematic review (SR) using the terms "Neoadjuvant therapy" AND "Thyroid carcinoma." Results: A 32-year-old man with a 7.8 cm (in the largest dimension) PTC was referred to total thyroidectomy, but tumor resection was not feasible due to extensive local invasion (trachea, esophagus and adjacent structures). Sorafenib, a multikinase inhibitor (MKI), was initiated; a 70% tumor reduction was observed after 6 months, allowing new surgical intervention and complete resection. Radioactive iodine was administered as adjuvant therapy, and whole body scan (WBS) shows uptake on thyroid bed. One-year post-surgery the patient is asymptomatic with a status of disease defined as an incomplete biochemical response. The SR retrieved 123 studies on neoadjuvant therapy use in thyroid carcinoma; of them, 6 were extracted: 4 case reports and 2 observational studies. Multikinase inhibitors (MKI) were used as neoadjuvant therapy in three cases with 70-84% of tumor reduction allowing surgery. Conclusion: Our findings, along with other reports, suggest that MKIs is an effective neoadjuvant therapy and should be considered as a therapeutic strategy for unresectable grossly locally invasive thyroid carcinomas.